VARIABEL ANTESEDEN KEPUASAN DAN PENGARUHNYA TERHADAP LOYALITAS KONSUMEN - Hanif Abdul Latif; Dwiwiyati Astogini; Sumarsono Sumarsono (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2016)
The purpose this study to identify and analyze the effect antecedent variable of satisfaction that is web design, web navigation, costumized preview, website quality, service quality, and perceived value to consumer loyalty of Lazada.co.id. The sample in this study there were 155 respondents who are consumers of Lazada.co.id in Jakarta region. Convenience sampling method used in the determination of the sample. Data was analyzed using Equational Structural Modeling (SEM). These results indicate web design has no effect on web quality, web navigation has positive effect on web quality, customized preview has no effect on web quality, web quality has no effect on perceived value, service quality has positive effect on perceived value, perceived value has positive effect on satisfaction,satisfaction has positive effect on consumer loyalty.